Peran Orang Tua dalam Pembinaan Akhlak Anak di Mendit Petanahan - Fitroh, Nisa Ul; Trisnawati, Oky Ristya (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The research objectives are: (1). To find out the role of parents in moral training for children in Dukuh Mendit, Kritig Village, Petanahan District, Kebumen Regency. (2). To find out the supporting and inhibiting factors for parents in developing children's morals in Dukuh Mendit, Kritig Village, Petanahan District, Kebumen Regency. The method used is a qualitative descriptive approach. Meanwhile, the research design is field research. Data was obtained from observations, interviews and documentation. And for data analysis the author uses analysis from Miles and Huberman. Data processing techniques use qualitative analysis which includes data reduction, data presentation and conclusions. The research results obtained: It is known that the role of parents is in developing children's morals through education, supervision and example. Parents in Dukuh Mendit have tried to implement the role of parents as educators by teaching religious knowledge, such as praying on time and reciting the Koran. The role of parents is by example by providing a good example, such as speaking politely to others, saying sorry when they make a mistake and thanking them. The role of parents is supervision by means of parents frequently checking their children's cellphones, advising their children when they make mistakes and making friends with good children. Supporting and inhibiting factors for parents in developing children's morals in Dukuh Mendit, Kritig Village. Supporting factors: Good communication between children and parents, protective attitude of parents to remind children to have good morals, enrolling children in TPQ. Inhibiting factors: Lack of parental education in developing morals, parents' busyness in working and children who are difficult to manage.